Exploring the Potential and Advancements of Circular RNA Therapeutics - Lei Wang; Lianqing Wang; Chunbo Dong; Jialong Liu; Guoxin Cui; Shan Gao; Zhida Liu (Exploration)
ABSTRACT Messenger RNA (mRNA) technology is revolutionizing the pharmaceutical industry owing to its superior safety profile, manufacturing capabilities, and potential applications in previously undruggable therapeutic targets. In addition to linear mRNA, such as conventional mRNA, self‐amplifying mRNA, and trans‐amplifying mRNA, circular mRNA has emerged as a promising candidate. Circular RNA (circRNA) is a class of single‐stranded RNA with a covalently closed loop structure that offers enhanced stability compared to linear RNA by resisting degradation from RNases. Recent studies have revolutionized our understanding of their biological functions, surpassing the notion that they are merely byproducts of aberrant splicing events. Given the remarkable success achieved in cancer and SARS‐CoV‐2/monkeypox virus (MPXV) vaccines, circRNA is being intensively investigated for gene and cell therapies. In this review, we provide an overview of circRNA biogenesis mechanisms in vivo, along with synthesis strategies in vitro, while discussing translation regulation mechanisms and quality control processes involved in circRNA production. Furthermore, we explore the potential application scenarios for circRNAs.